Plagiarism Awareness among University Undergraduates: A Study on Final Year Students - Zainuddin, Intan Suriani; Ahmad Helmi, Siti Aisyah Humaira; Pek, Lim Seong; Mee, Rita Wong Mee (Selangor Humaniora Review, 2021)
Plagiarism is an act of dishonesty that occurs in higher education for over decades. Some people are still unaware of plagiarism and the factors that can contribute to it due to lack of plagiarism exposure, especially among higher education undergraduates. Therefore, this study investigates the awareness of plagiarism among final year TESL (Teaching English as Second Language) undergraduates and determines the factors influencing TESL undergraduates to plagiarise. A total of 33 respondents participated in this quantitative survey. Twenty-three adapted questions were randomly distributed to the TESL undergraduates using Google Form divided into two sections. Based on the findings, the respondents indicated that they are highly aware of plagiarism. The highest factor that influenced the TESL undergraduates to plagiarise was due to short deadlines of assessments. Therefore, this suggests that the institution imparts knowledge on plagiarism to TESL undergraduates by setting up plagiarism workshops. This study is hoped to provide insight into the current awareness of plagiarism in the local context.